Carbon buffered-transition metal oxidenanoparticle-graphene hybrid nanosheets as high-performance anode materials for lithium ion batteries - Huang, Xin (2014)
In this article, we report a simple and general method for the synthesis of carbon buffered-metal oxidenanoparticle (NP)–graphene hybrid 2D nanosheets, which include C-SnO2–rGO and C-Fe2O3–rGO nanosheets. For the preparation of these anodes, tannic acid (TA), a kind of polyphenol extracted from plants, was used as a dispersing agent to introduce a metal precursor on the surface of rGO, and the metal precursor was subsequently converted to the corresponding metal oxide NPs by thermal annealing in a vacuum. During the thermal annealing process, TA was decomposed to form carbon materials, which acted as a buffering matrix to effectively suppress the aggregation and pulverization of the active NPs during the electrochemical performances. It is found that the as-prepared C-SnO2–rGO and C-Fe2O3–rGO nanosheets both exhibited high reversible capacity and rate capability. After 100 discharge/charge cycles, the C-SnO2–rGO nanosheet delivered the reversible capacity of 633.2 mA h g−1 at a current density of 200 mA g−1 with extremely low capacity fading (0.32 mA h g−1 per cycle), and it can deliver discharge capacities of 641.3, 526.5, 452.7, 408.1 and 379.5 mA h g−1 in the 10th cycle at current densities of 200, 400, 800, 1200 and 1600 mA g−1, respectively. Upon return to a cycling rate of 200 mA g−1, the C-SnO2–rGO can maintain a specific capacity of 607.0 mA h g−1 even after 35 cycles. As for the C-Fe2O3–rGO nanosheet, it can deliver 504.1 mA h g−1 at a current density of 500 mA g−1 after 100 cycles, and the corresponding discharge capacities in the 10th cycle at current densities of 1000, 1500 and 2000 mA g−1 are 365.9, 319.0 and 288.6 mA h g−1, respectively.